2011
DOI: 10.1093/eurpub/ckr057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of false-positive results on reattendance at breast cancer screening programmes in Spain

Abstract: A false-positive screening mammogram in the first screening negatively affected attendance at the subsequent screening. The results of this study could be useful to improve the screening process and to increase women's compliance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…The negative effect of false positives on screening retention is consistent with the findings from two-decade-old Canadian studies 11,21 and a more recent study conducted in Spain, where breast cancer screening is also free and is recommended biennially. 22 Retention rates were higher in the Spanish study than in ours: retention rates for women with false positive vs. normal results were 78.3% vs. 81.9%, compared to ours which were 68.1% vs. 68.7% respectively. Both studies found significantly lower retention rates, 66.5% (Spain) and 45.8% (Alberta) for those who underwent invasive procedures, including aspiration, closed biopsy and/or open biopsy.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…The negative effect of false positives on screening retention is consistent with the findings from two-decade-old Canadian studies 11,21 and a more recent study conducted in Spain, where breast cancer screening is also free and is recommended biennially. 22 Retention rates were higher in the Spanish study than in ours: retention rates for women with false positive vs. normal results were 78.3% vs. 81.9%, compared to ours which were 68.1% vs. 68.7% respectively. Both studies found significantly lower retention rates, 66.5% (Spain) and 45.8% (Alberta) for those who underwent invasive procedures, including aspiration, closed biopsy and/or open biopsy.…”
Section: Discussioncontrasting
confidence: 64%
“…Both studies found significantly lower retention rates, 66.5% (Spain) and 45.8% (Alberta) for those who underwent invasive procedures, including aspiration, closed biopsy and/or open biopsy. 22 Invasive follow-up tests have been shown to create psychological distress in the context of false positive breast cancer screens, 23 which can last for up to three years; 7,24 it is likely that psychological distress plays an important role in screening retention.…”
Section: Discussionmentioning
confidence: 99%
“…The study size was comparable with similar studies performed in other countries 7,10,12,14 , although significantly smaller than some very large studies. 15,17,18 The screening services included in the study represent a balanced cross-section of the population in different parts of the country, and include ethnic minority communities and rural and inner city populations. Indices of multiple deprivation (IMDs) were obtained for those Primary Care Trusts (PCTs -the local commissioners of health care during the study period) whose main screening provider was one of the five programmes included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The meta-analysis was updated in 2011 16 with the addition of another two European studies 12,13 but with no change in the conclusion. Two further European studies 15,17 and a recently published study from Australia 18 found that false positive screening reduced subsequent attendance whereas a study of the Irish BreastCheck programme 14 found a small but significant increase in reattendance following false positive mammography.…”
mentioning
confidence: 99%
“…45 Absenting from screening consequently negates any benefits of the service and increases the mortality rate. 46 To ensure accurate and low falsepositive recall rates it is important to regularly measure screening performance parameters and provide feedback to screening personnel. 47 …”
Section: Psychological Impact Of Recallmentioning
confidence: 99%